2016
DOI: 10.1016/j.lwt.2016.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the efficacy of ultrasound combined with essential oils on the decontamination of Salmonella inoculated lettuce leaves

Abstract: a b s t r a c tSalmonella is one of main pathogenic bacteria present in fresh produce. Ultrasound has been reported to be effective at inactivating food-borne pathogens. Moreover, ultrasound can be combined with essential oils to enhance its efficacy. This study evaluates the reduction and inactivation of Salmonella enterica Abony inoculated on lettuce leaves by the application of continuous and pulsed ultrasound as well as ultrasound combined with the essential oil of oregano and thyme. The physicochemical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…However, combination treatment with 1.5 mg/L of ozone for 4 min can prevent cross‐contamination by inactivating bacterial population in washing water below the limited of detection of 1.0 log CFU/ml. Similar observations were reported in numerous studies which have investigated the ability of combination treatment of ultrasound to inactivate microorganisms on fresh product (Alves do Rosario et al., 2017; Gomez‐Lopez, Gil, Allende, Vanhee, & Selma, 2015; Huang et al., 2018; Millan‐Sango, Garroni, Farrugia, Van Impe, & Valdramidis, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…However, combination treatment with 1.5 mg/L of ozone for 4 min can prevent cross‐contamination by inactivating bacterial population in washing water below the limited of detection of 1.0 log CFU/ml. Similar observations were reported in numerous studies which have investigated the ability of combination treatment of ultrasound to inactivate microorganisms on fresh product (Alves do Rosario et al., 2017; Gomez‐Lopez, Gil, Allende, Vanhee, & Selma, 2015; Huang et al., 2018; Millan‐Sango, Garroni, Farrugia, Van Impe, & Valdramidis, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…It was found that US in continuous mode decreased Salmonella to 2.2 log CFU/cm 2 . However, US combined with essential oils enhanced the bacterial reduction on lettuce leaves (Millan‐Sango, Garroni, Farrugia, Van Impe, & Valdramidis, ).…”
Section: Resultsmentioning
confidence: 99%
“…When the studies in which changes in the inactivation of pathogenic microorganisms, quality parameters of food products and products in the activation of enzymes are analyzed, successful results were obtained [100][101][102][103][104][105][106][107].…”
Section: Ultrasonicationmentioning
confidence: 99%